2022
DOI: 10.15586/ijfs.v34i2.2141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-moisture extrusion on soy meat analog: study on its morphological and physiochemical properties

Abstract: There has been a growing interest in meat analog, microstructure characteristics, and anti-nutritional content obtained from soybean. High-moisture extrusion parameters are the input extruder of moisture content (>40%) that get the advantages of lower energy input. Thermo-mechanical treatment has a considerable influence on structural properties of soy-based meat analog. Texturized soy proteins can substitute meat products while providing a high-protein food ingredient which can be consumed directly as meat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Studies have shown that at low moisture content (<36%) protein denaturation occurs when the temperature exceeds 140 °C. 26 At temperature 150 °C, the protein did not undergo the melting process, leading to a notably low expansion rate and consequently resulting in diminished digestibility. As the extrusion temperature increased, the protein progressively underwent both melting and denaturation processes, inducing a Note: Results are expressed as mean ± SD (n = 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that at low moisture content (<36%) protein denaturation occurs when the temperature exceeds 140 °C. 26 At temperature 150 °C, the protein did not undergo the melting process, leading to a notably low expansion rate and consequently resulting in diminished digestibility. As the extrusion temperature increased, the protein progressively underwent both melting and denaturation processes, inducing a Note: Results are expressed as mean ± SD (n = 3).…”
Section: Discussionmentioning
confidence: 99%
“…The overall trend of digestibility is downward with temperatures from 160 to 190 °C, probably because excessive extrusion temperatures may result in protein charring. 26,27 The interaction of temperature and screw speed during extrusion can alter protein conformation and in vitro protein digestibility. 28 Our results also showed that a screw speed of 24 rpm leads to unattractive textural properties and digestibility of ESPro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The production and the characterization of texturized proteins have been previously reported in several studies, in which different protein isolates are commonly used, such as pea and oat (Kaleda et al, 2020); soy and microalgae (Caporgno et al, 2020); soy (Islam et al, 2022); rapeseed (Jia et al, 2021); and soy, mung bean, peanut, pea, and wheat gluten (Samard and Ryu, 2019). However, it should be considered that the protein isolates are extracted and concentrated by using a high resourcedemanding process, generally defined as "wet extraction" (Lie-Piang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%